SPR‐based plastic optical fibre biosensor for the detection of C‐reactive protein in serum. Issue 10 (18th April 2016) - Aray, Ayda; Chiavaioli, Francesco; Arjmand, Mojtaba; Trono, Cosimo; Tombelli, Sara; Giannetti, Ambra; Cennamo, Nunzio; Soltanolkotabi, Mahmood; Zeni, Luigi; Baldini, Francesco
Abstract : A plastic optical fibre biosensor based on surface plasmon resonance for the detection of C‐reactive protein (CRP) in serum is proposed. The biosensor was integrated into a home‐made thermo‐stabilized microfluidic system that allows avoiding any thermal and/or mechanical fluctuation and maintaining the best stable conditions during the measurements. A working range of 0.006–70 mg L –1 and a limit of detection of 0.009 mg L –1 were achieved. These results are among the best compared to other SPR‐based biosensors for CRP detection, especially considering that they were achieved in a real and complex medium, i.e. serum. In addition, since the sensor performances satisfy those requested in physiologically‐relevant clinical applications, the whole biosensing platform could well address high sensitive, easy to realize, real‐time, label‐free, portable and low cost diagnosis of CRP for future lab‐on‐a‐chip applications.3D sketch (left) of the thermo‐stabilized home‐made flow cell developed to house the SPR‐based plastic optical fibre biosensor. Exemplary response curve (shift of the SPR wavelength versus time) of the proposed biosensor (right) for the detection of C‐reactive protein in serum. Abstract : A surface plasmon resonance‐based biosensor implemented on a plastic optical fibre for the selective detection of C‐reactive protein in a real and complex matrix (i.e. serum) is presented. With detection limit of 9 µg L –1 (below that requested in clinical applications), the proposed biosensing platform, integrated into a home‐made thermo‐stabilized flow cell, could underpin the need for high sensitive, real‐time, label‐free, portable and low cost platforms for future lab‐on‐a‐chip applications.